“The boundaries spanning”: How public relations able to bridge between organization and community - Muchtar, Khoiruddin; Nurhidayat, Dedi; Suherdiana, Dadan; Rosyidi, Imron; Fitri, Susanti Ainul (Program Studi Ilmu Komunikasi, 2026)
Public relations (PR) is crucial for shaping a positive organizational image and fostering constructive relationships with the public. This study analyzes the PR strategy of the Partai Keadilan Sejahtera (Prosperous Justice Party) Regional Leadership Council (DPW PKS) in West Java. Using a descriptive qualitative approach and a case study method, data were collected through indepth interviews, non-participatory observation, and documentation analysis. Thematic examination followed. Findings show that DPW PKS’s PR bridges the party and the public by promoting transparency, inclusive dialogue, and participatory engagement. Proactive issue management and rapid responses to disinformation help maintain the party’s reputation amid dynamic political contexts. Internally, cohesive communication and member welfare reinforce integrity. Externally, collaboration with media, government, and communities enhances credibility and long-term public trust in digital democracy.